Evaluating a project in creative & arts (Digital) and how a project can run Successfully in digital platform department in context of Ogilvy Bangladesh - Tasnim, Farzana (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.